A framework for decision-making within strength and conditioning coaching. - Till, K.; Muir, B.; Abraham, A.; Piggott, D.; Tee, J. (Strength and Conditioning Journal, 2019)
Decision-making is a key factor in developing coach expertise and effectiveness. This article presents a framework for enhancing coach decision-making within strength and conditioning (s&c). Based on theoretical understanding of the athlete (the "who"), s&c training principles and sport demands (the "what"), and learning theories and behavior (the "how"), coaches can enhance s&c practice ("planning, delivering, and reflecting"). In addition, understanding contextual challenges ("context, culture, and politics") and own beliefs, values, and behaviors ("self") must be considered. Recommendations are presented for implementing constructively aligned learning programs based on the decision-making framework for enhancing coach learning and professional development within s&c.